Integration of Efficacy Values in Comparison of Legal Systems: A Reform Perspective - Ade Saptomo; Badrunsyah Badrunsyah; Merry Aryanti (Fakultas Hukum, Universitas Warmadewa, 2025)
The Indonesian legal system still focuses on a normative approach that lacks real benefits for society. The utilitarian approach applied in various global legal systems can improve the application of laws that are more efficient and fairer. This study aims to analysed the integration of utility value in the comparison of legal systems and legal reform in Indonesia. The method used is a comparative analysis of legal systems through literature studies on the application of utility in law in the United Kingdom, Japan, and Continental European countries. The application of the value of utility can increase the effectiveness and fairness of the legal system. Countries with this approach show legal solutions that are more responsive to social needs. The integration of utility values in the Indonesian legal system is important to create a more efficient and fair legal system.